Cumulative attraction and spatial dependence in a destination choice model for beach recreation. (June 2018) - Matthews, Yvonne; Scarpa, Riccardo; Marsh, Dan
Abstract: The destination choices of individual recreationalists are dependent on the spatial distribution of sites and attractions. An important issue in destination choice modelling is how to account for the effects of cumulative attraction from multiple sites and hierarchical processing of potential destinations. This study is concerned with recreational visits to beaches on the Coromandel Peninsula of New Zealand. Each beach has a different combination of attractions with potentially complex substitution patterns. We find that an Agglomerating and Competing Destination Choice model, with differentiated accessibility parameters for each attribute, offers the best fit. It is flexible enough to model different levels of substitutability for different attraction types, yet is tractable in estimation. We compare response predictions of different models for two site-specific changes - closure of a campground and construction of a sea wall. Allowing for more complex substitution patterns results in different predictions for visitation in the wider area. Highlights: The beach destination choices of domestic tourists in New Zealand are analysed. The spatial distribution of beach amenities is an important consideration in choice. We include complement and substitute accessibility parameters for each attribute. The implications of two site changes are compared for different models.